ANALYSIS OF THE PROFITABILITY - FINANCIAL POSITION CORRELATION - CĂRUNTU GENU ALEXANDRU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Evaluating a business' financial performance and profitability is a fundamental element of financial management, having a considerable impact on long-term success. In today's context, it is essential for a manager to be well informed about the current state of the business and to be able to react promptly to changes that could negatively influence its value, thus diminishing returns for investors, even in the absence of a financial crisis . The main objective of this topic is to apply financial analysis methods to identify the performance and financial health of the analyzed company, based on profitability rates and financial indicators that reflect its position. In addition, recommendations will be made to improve the current situation. To achieve this goal, the paper will use the methods of description, analysis, comparison and synthesis. . Economic-financial analysis plays an essential role in understanding the current context and in ensuring favorable results in the future. The evaluation of financial statements is fundamental to carry out a complete diagnosis of the profitability and financial stability of a company, representing a basic element in the analysis of financial performance. Performance refers to the realization of activities that require specific skills. In the case of an organization, it reflects the ability to achieve set goals. In certain circumstances, it may be necessary to temporarily abandon the principles of economic rationality in order to access new markets or maintain existing products. This forgoing of short-term profit should lead to higher future profits. Profitability assessment involves calculating the difference between income and resources consumed, with the aim of increasing the wealth of the owners by distributing dividends or increasing equity.